2021
DOI: 10.1021/acsami.1c06520
|View full text |Cite
|
Sign up to set email alerts
|

Multistructured Electrospun Nanofibers for Air Filtration: A Review

Abstract: Air filtration materials (AFMs) have gradually become a research hotspot on account of the increasing attention paid to the global air quality problem. However, most AFMs cannot balance the contradiction between high filtration efficiency and low pressure drop. Electrospinning nanofibers have a large surface area to volume ratio, an adjustable porous structure, and a simple preparation process that make them an appropriate candidate for filtration materials. Therefore, electrospun nanofibers have attracted inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
203
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(204 citation statements)
references
References 170 publications
(284 reference statements)
0
203
1
Order By: Relevance
“…In comparison, the nanofiber membrane fabricated by electrospinning technology has superior characteristics of thin diameter, large specific surface area, interconnected pore structure, and high porosity, which are conducive to high interception and capture of tiny aerosol particles [10][11][12]. Under unremitting researches, a large amount of high molecular polymer materials, such as PVDF, PSA, PAN, and PMIA, have been successfully fabricated by the electrospinning method [13][14][15][16]. Ding et al reported an integrated microfiber, nanofiber and nanonets filter by a combination of three layers with different fiber diameters in sequence [17].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the nanofiber membrane fabricated by electrospinning technology has superior characteristics of thin diameter, large specific surface area, interconnected pore structure, and high porosity, which are conducive to high interception and capture of tiny aerosol particles [10][11][12]. Under unremitting researches, a large amount of high molecular polymer materials, such as PVDF, PSA, PAN, and PMIA, have been successfully fabricated by the electrospinning method [13][14][15][16]. Ding et al reported an integrated microfiber, nanofiber and nanonets filter by a combination of three layers with different fiber diameters in sequence [17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the electrostatic and chemical interaction between the filter and the particulate can also significantly affect the filtration performance [14,17]. Recently also the efficiency of electrospun fibers in air filtration was summarized by Lu and coworkers, emphasizing all the morphological properties that allow the air filtration efficiency to be improved [18].…”
Section: Propertiesmentioning
confidence: 99%
“…An environmental study has shown that prolonged exposure to these particles increases mortality due to COVID-19. In fact, particles with high surface-to-volume ratios can absorb the virus-containing SARS-CoV-2 and spread viral infection [ [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%